Pengembangan Sistem Pakar Berbasis Fuzzy MADM dengan Metode SAW untuk Prioritas Penanganan Gejala Depresi - Febrian Sania Putri Vina; Sutarman Sutarman (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Depression is a mental health disorder that is often unrecognized and can develop into a more serious issue if not addressed properly. One of the main challenges in managing depression is the lack of tools that can objectively measure the severity of symptoms and determine who requires immediate treatment. This study aims to develop an expert system based on Fuzzy Multiple Attribute Decision Making (MADM) with the Simple Additive Weighting (SAW) method to prioritize the treatment of depression symptoms based on criteria such as intensity, duration, and impact on daily life. The system goes through several stages, including data pre-processing, fuzzification, criterion weighting, decision matrix normalization, and ranking calculation using SAW, resulting in an accurate treatment priority ranking. The research findings show that this system can assist healthcare professionals in identifying individuals with the most severe symptoms who require immediate intervention, thereby speeding up treatment and improving the effectiveness of therapy provided.